STRATEGI PEMBERDAYAAN MELALUI PERAN SATGAS WILAYAH DALAM PENANGANAN KONFLIK SOSIAL DAN KEAMANAN DI KABUPATEN PUNCAK JAYA - Agustina Setiawan; Mamat Sonjaya; Dicky Febriansyah Rokhmat (Jurnal Caraka Prabu, 2024)
In an attempt to maintain the integrity of the Republic of Indonesia in the Papua Region, the government, through the TNI, formed a Territorial Task Force. This research aims to analyze the strategy for empowering the Papua defense region through the role of the Territorial Task Force in handling social and security conflicts in Puncak Jaya Regency. This research uses Strategy theory according to Thomas Schelling, namely management instruments for survival and winning competition. This research uses qualitative research methods, and data collection techniques use observation, interviews, documentation. The biggest challenge to conditions in Puncak Jaya is the conflict between the KKB and the community or with the TNI/Polri. Based on the results of the research, the strategic approach taken by the Territorial Task Force in fostering and empowering conflict areas in Puncak Regency is the strategic approach taken by the Territorial Task Force in fostering and empowering conflict areas still continues today, the strategy used is first, a private approach by providing outreach in every sub-district in Puncak Jaya Regency; Second, an approach in the form of free health checks; Third, collaborate with the regional government to carry out outreach to the community; Fourth, provide command posts in each sub-district to monitor and maintain security and establish relations with the community; Fifth, collaborate with the community, especially the Family Welfare Empowerment Group (PKK) to direct and be the first implementer in empowering conflict areas